Metodologi Tafsir Al-Quran Kontemporer dalam Pemikiran Fazlur Rahman - Syukri, Ahmad (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This report studies the methodology of contemporary Quranic exegesis in the thought of Fazlur Rahman (1332-1408/1919-1988). He observes that in interpreting the Quran, classical and modern methodologies are no longer conducive to the life of Muslims nowadays. There is a basic need to discover a new method to interpret the Quran which is suitable to the contemporary demand. Thus, the Quran must be studied through the method of double movement. A method which offers an impartial treatment to the message of the Quran and welfare of human life This study is approached by using historical, comparative, and content analysis.